Macromolecular crowding studies of amino acids using NMR diffusion measurements and molecular dynamics simulations - Virk, Amninder S.; Stait-Gardner, Timothy; Willis, Scott A.; Torres, Allan M.; Price, William S. (Frontiers in Physics, 2015)
Molecular crowding occurs when the total concentration of macromolecular species in a solution is so high that a considerable proportion of the volume is physically occupied and therefore not accessible to other molecules. This results in significant changes in the solution properties of the molecules in such systems. Macromolecular crowding is ubiquitous in biological systems due to the generally high intracellular protein concentrations. The major hindrance to understanding crowding is the lack of direct comparison of experimental data with theoretical or simulated data. Self-diffusion is sensitive to changes in the molecular weight and shape of the diffusing species, and the available diffusion space (i.e., diffusive obstruction). Consequently, diffusion measurements are a direct means for probing crowded systems including the self-association of molecules. In this work, nuclear magnetic resonance (NMR) measurements of the self-diffusion of four amino acids (glycine, alanine, valine and phenylalanine) up to their solubility limit in water were compared directly with molecular dynamics simulations. The experimental data were then analyzed using various models of aggregation and obstruction. Both experimental and simulated data revealed that the diffusion of both water and the amino acids were sensitive to the amino acid concentration. The direct comparison of the simulated and experimental data afforded greater insights into the aggregation and obstruction properties of each amino acid.